Panel Discussion (Hematology Meeting Reports, 2009)
Dr. Joshua, Symposium Chair: Patients commonly ask about the risks associated with thalidomide and whether they should take the drug early or wait until relapse occurs. Will early or late therapy make a difference for patients? Dr. San Miguel: It is probably better to start thalidomide treatment early, but we have no data to support that recommendation. Several studies are under way to address this question.